2020
DOI: 10.21203/rs.3.rs-24584/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Level and Predicators of quality of Integrated Disease Surveillance and Response for Infectious Disease in Tigray, Northern Ethiopia: Cross-Sectional Study

Abstract: Background: The health impacts of recent global infectious disease outbreaks have demonstrated the importance of strengthening public health systems. The aim of the study was to assess the level of quality of integrated disease surveillance and response for infectious disease in public health facilities of Tigray, Northern Ethiopia. Methods: the study was facility based cross-sectional. It was conducted from June- July 2018 in 46 health facilities. It has involved mixed method approach both quantitative and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
(27 reference statements)
0
4
1
Order By: Relevance
“…This finding is higher than the study done in Jordan 13 and the Eastern part of Nigeria 21 in which only 39.50% and 25.20% of health-care providers had a good level of IDSR practice, respectively. On the contrary, the result of this study showed a lower level of IDRS practice compared to the study conducted in Egypt, 14 Nigeria, 27 Kingdom of Bahrain 8 and in the Tigray region of Ethiopia, 19 which revealed 68.70%, 63.50%, 80.01%, and 80.40% good level of IDSR practice, respectively. The reason for this discrepancy might be knowledge differences, low organizational support, the country’s educational curriculum, and the complexity of reporting systems and study areas.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…This finding is higher than the study done in Jordan 13 and the Eastern part of Nigeria 21 in which only 39.50% and 25.20% of health-care providers had a good level of IDSR practice, respectively. On the contrary, the result of this study showed a lower level of IDRS practice compared to the study conducted in Egypt, 14 Nigeria, 27 Kingdom of Bahrain 8 and in the Tigray region of Ethiopia, 19 which revealed 68.70%, 63.50%, 80.01%, and 80.40% good level of IDSR practice, respectively. The reason for this discrepancy might be knowledge differences, low organizational support, the country’s educational curriculum, and the complexity of reporting systems and study areas.…”
Section: Discussioncontrasting
confidence: 94%
“…A total score of 20 and above was taken as good, and a score less than 20 was considered poor. 19 Perceived technical competency of IDSR: is defined in terms of data collection design, use of technology for data entry, analysis, and format friendly and measured by Five Point Likert scale questionnaire. A total of six questions were computed to construct the technical competency factor and scored out of 30, a score of 24 and above was reported as good technical competency, and a score less than 24 was reported as poor technical competency.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations